2013
DOI: 10.1007/s11096-013-9798-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of drug-related problems by a clinical pharmacist in addition to computerized alerts

Abstract: As most DRPs identified by a clinical pharmacist were not detected in daily clinical practice by CPOE/CDSS, a clinical pharmacist contributes to reducing DRPs. The sensitivity of CPOE/CDSS to detect certain classes of problems should be optimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 42 publications
3
42
1
4
Order By: Relevance
“…Efforts to increase the specificity of DDI alerts by understanding DDI burden and adding information regarding their clinical relevance should be encouraged . Adherence to the guidelines could also be enhanced by increasing the role of the pharmacist in responding to DDI alerts . Because the co‐medication of metoprolol–paroxetine/fluoxetine is still observed, a decision should be made whether the interaction is deemed sufficiently clinically significant to keep it in both surveillance systems, G‐Standard and Pharmabase.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to increase the specificity of DDI alerts by understanding DDI burden and adding information regarding their clinical relevance should be encouraged . Adherence to the guidelines could also be enhanced by increasing the role of the pharmacist in responding to DDI alerts . Because the co‐medication of metoprolol–paroxetine/fluoxetine is still observed, a decision should be made whether the interaction is deemed sufficiently clinically significant to keep it in both surveillance systems, G‐Standard and Pharmabase.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, CPOE use has improved patient safety, prevented medical errors, and facilitated communication between physicians and pharmacists . The PRESCRIB Project established an innovative strategy that further develops the CPOE capabilities introduced some years ago by our hospital pharmacy.…”
Section: Discussionmentioning
confidence: 87%
“…Hepler and strand defines DRPs as "A drug related problem is an event or circumstances involving drug treatment that actually or potentially in DRPs frequency have been reported. Rianne reported 442 DRPs in 228 patients in study, 25 this showed 736 DRPs in 196 patients. 26 The lack of standardized method for identifying DRP restricts the possibility in such area.…”
Section: Drug Related Problemsmentioning
confidence: 90%